P168 Rifabutin is a useful alternative to rifampicin in the treatment of active TB/HIV co-infection. (16th November 2010) - Singh, R; Marshall, N; Reynolds, C J; Breen, R A M; Smith, C J; Swaden, L; Bhagani, S; Hopkins, S; Johnson, M A; Lipman, M C I
Abstract : Introduction: Effectiveshort course anti-tuberculosis treatment (TB Rx) requires use of a rifamycin, typically rifampicin (RIF). However, in patients with TB/HIV co-infection it has significant drug interactions; and rifabutin (RBT) is often substituted in those taking anti-retrovirals (ARVs). Recent data suggest that the recommended dosage of RBT may be inadequate with concomitant ARVs, leading to an increased risk of subsequent rifamycin resistance after apparent successful treatment. Aims: We undertook a retrospective, single-site review of TB/HIV treatment to determine the impact of rifamycin selection on prevalence of serious (ACTG grade III or IV) adverse events (AE), TB treatment completion and TB recurrence. Methods: The characteristics and treatment outcomes, stratified by rifamycin type and ARV use for all adults with TB/HIV co-infection receiving rifamycin-based therapy as part of active TB Rx from 1997 to 2008 were examined. Rifamycin choice and dosage was in line with BHIVA guidance for TB/HIV therapy—in general RIF being used with a non-nucleoside inhibitor ARV combination and RBT with boosted protease inhibitors. Results: 143 HIV-positive individuals received rifamycin-based TB Rx during the study period (64 RIF, 56 RBT and 24 RIF/RBT in treatment switch—see Abstract P168 Table 1 ). 103/143 (72%) patients had culture positive disease, of whom 4 had isoniazid drug resistance. 106/143 (74%) patients used ARVs during TB Rx. Patients on ARVs who had RIF either alone, or switched from RIF to RBT during TB Rx had a higher incidence of serious AE compared to those prescribed RBT alone (p=0.002). There was no difference in the percentage of patients who completed prescribed TB Rx between the RIF and RBT groups (p=0.6). After a median follow-up of 3.2 years from start of TB Rx, 4 patients relapsed, all with a drug sensitive organism. Conclusion: Within our study population, rifabutin is a useful alternative to rifampicin in the treatment of active TB/HIV co-infection and does not appear to lead to subsequent rifamycin resistance after successful therapy. We find no evidence in this analysis to change the advice within the current national TB/HIV guidelines.